2003
DOI: 10.1089/104454703322650194
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Temperature Changes in Dentine

Abstract: A maximum rise of mean temperature to 1.68 degrees C in closest vicinity to the pulpal chamber and the morphological unaltered dentine surfaces demonstrate the safe and tissue preserving character of the superpulsed 9.6 microm CO2 laser. The laser caused an even lower temperature rise than conventional drilling. Moreover, the laser showed acceptable efficacy with ablation rates that did not significantly differ from the conventional dental drill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In this study, we used a super pulsed CO 2 laser at very low energy density (less than 12.5 J/cm 2 ). Previous studies (22, 28, 29) have reported that irradiation with a CO 2 laser at very low energy did not change the surface morphology of enamel, dentin, or bone and did not influence the temperatures of pulp and the dentin surface, suggesting that irradiation with a CO 2 laser at very low energy density might decrease periodontopathic bacteria and LPS without damaging the hard tissues adjacent to the subgingival area.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, we used a super pulsed CO 2 laser at very low energy density (less than 12.5 J/cm 2 ). Previous studies (22, 28, 29) have reported that irradiation with a CO 2 laser at very low energy did not change the surface morphology of enamel, dentin, or bone and did not influence the temperatures of pulp and the dentin surface, suggesting that irradiation with a CO 2 laser at very low energy density might decrease periodontopathic bacteria and LPS without damaging the hard tissues adjacent to the subgingival area.…”
Section: Discussionmentioning
confidence: 90%
“…The use of a pulsed CO 2 laser may decrease thermal damage (18, 20). It has been reported (21, 22) that dental pulp irradiated with a super pulsed laser for a short time showed temperature increases within physiologically acceptable limits, suggesting that the super pulsed laser does not cause thermal damage. Therefore, we hypothesized that irradiation by a super pulsed CO 2 laser at lower energy density would have few adverse effects on dental hard tissue and could safely be used in the subgingival area.…”
mentioning
confidence: 99%
“…Some Er:YAG laser beams could penetrate to deeper areas than the ablated area and damage the nerve fi bres and terminals, which might be a mecha nism of pain reduction in cavity ablation with the Er:YAG laser. 1 A number of authors 10,13,16,[18][19][20][21][22][23] stud ied the behaviour of different lasers to determine the amount of temperature increase during cavity preparation on dental structure. Keller et al (2003) 19 verified a mean temperature rise of 1.68ºC in the pulpal chamber using CO 2 and morphologically unaltered dentine surfaces, demonstrat ing the safe and tissue preserving char acter of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…1 A number of authors 10,13,16,[18][19][20][21][22][23] stud ied the behaviour of different lasers to determine the amount of temperature increase during cavity preparation on dental structure. Keller et al (2003) 19 verified a mean temperature rise of 1.68ºC in the pulpal chamber using CO 2 and morphologically unaltered dentine surfaces, demonstrat ing the safe and tissue preserving char acter of the laser. But Malmstrom et al (2001) 21 using pulsed CO 2 laser light for soft tissue surgery found detrimental changes to oral hard tissue and to the pulp.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the replacement is prohibitively expensive. In addition, studies have shown that water laser can still increase the temperature of the dental surface, pulp chamber, and soft tissue, though the water cooling significantly suppresses this effect compared to the case of the high-speed dental drill [12,13]. These shortcomings may limit the application of water lasers in health care.…”
Section: Introductionmentioning
confidence: 99%